Fluorescent ceramics and manufacturing method thereof, light-emitting device and projection device
Patent Information
- Application Number
- JP2022519736
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-11-26
- Filing Date
- 2020-11-26
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-11-26
AI Technical Summary
Pure-phase fluorescent ceramics have low luminous efficiency due to their structure, making it difficult to achieve a high utilization rate for excitation light sources.
The development of fluorescent ceramics with a matrix containing luminescent centers and scattering units with varying refractive indices, where the first scattering unit has a higher refractive index than the luminescent center and the second scattering unit has a lower refractive index, enhancing light scattering and reducing lateral conduction within the ceramic.
This design improves fluorescence scattering performance and increases the light efficiency utilization rate by lengthening the optical path length and concentrating fluorescence emission in a small area near the incident laser light source.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fluorescent ceramics, and particularly to fluorescent ceramics, a method for manufacturing the same, a light-emitting device, and a projection device.
Background Art
[0002] Unlike pure-phase ceramics of YAG, YAG fluorescent ceramics can have light-emitting performance by doping YAG with lanthanoid elements such as cerium, substituting a small amount of yttrium positions with the element, and can convert incident light into light with a longer wavelength.
Summary of the Invention
Problems to be Solved by the Invention
[0003] The inventor of the present application has found in the process of long-term research and development that it is important to improve the luminous efficiency of fluorescent ceramics. Due to its own structure, pure-phase ceramics in fluorescent ceramics are difficult to have a high utilization rate for an excitation light source. When the fluorescent ceramics are excited, the number of its light-emitting centers is relatively small, so its luminous efficiency is low.
[0004] Therefore, in order to improve the luminous efficiency of current transparent fluorescent ceramics, new fluorescent ceramics are needed.
Means for Solving the Problems
[0005] The present application provides a fluorescent ceramic, a method for manufacturing the same, a light-emitting device, and a projection device, which can improve the scattering performance of the fluorescent ceramic with respect to fluorescence and improve the light efficiency utilization rate in a light source system.
[0006] In one aspect, the present invention provides a fluorescent ceramic comprising a matrix and at least a light-emitting center, a first scattering unit, and a second scattering unit distributed within the matrix, wherein the refractive index of the first scattering unit is greater than that of the light-emitting center, and the refractive index of the second scattering unit is less than that of the light-emitting center.
[0007] In other aspects, the present invention provides a method for manufacturing fluorescent ceramics, the manufacturing method comprising: preparing a matrix material, a scattering material, and phosphor particles of fluorescent ceramics in predetermined ratios, wherein the scattering material includes at least a pore-forming agent and first scattering particles and second scattering particles; obtaining a first ball mill slurry by mixing the matrix material and scattering material in a first solvent and ball milling; obtaining a second ball mill slurry by mixing the phosphor particles in a second solvent and ball milling; drying the first ball mill slurry and the second ball mill slurry, then polishing and sieving them to obtain a first powder and a second powder; mixing the first powder and the second powder and pressing the mixed powder to obtain a pre-molded product; obtaining a base material by high-temperature adhesive discharge treatment of the pre-molded product; cold isostatic pressurizing treatment of the base material; and obtaining fluorescent ceramics after performing high-temperature sintering treatment and polishing on the cold isostatic pressurized base material.
[0008] In another aspect, the present invention provides a light-emitting device comprising an excitation light source and the above-mentioned fluorescent ceramics, wherein the excitation light source is an incident laser light source.
[0009] In another aspect, the present application provides a projection device, which includes the above-mentioned light-emitting device. [Effects of the Invention]
[0010] The beneficial effects of this invention are as follows: Unlike the prior art, in this invention, the luminescence center, first scattering unit, and second scattering unit, each having a different refractive index, are uniformly distributed in the matrix of the fluorescent ceramics, and the refractive index of the first scattering unit is greater than that of the luminescence center, while the refractive index of the second scattering unit is smaller than that of the luminescence center. Since the particle scattering capability depends on the particle's dimension and relative refractive index, the incident laser light is scattered at the interface of each phase, thereby enhancing the refraction and scattering effects of the fluorescent ceramics on the incident laser light and fluorescence within them. This increases the optical path length of the excitation light in the ceramics, further weakens the lateral conduction of fluorescence within the fluorescent ceramics, and ultimately causes the fluorescence to scatter from a small area near the incident laser light, i.e., the generated fluorescence spot is small, further improving the scattering performance of the fluorescent ceramics on fluorescence. [Brief explanation of the drawing]
[0011] To more clearly explain the technical solutions in the embodiments of this application, the drawings necessary for describing the embodiments are briefly introduced below. Clearly, the drawings described below represent only a few embodiments of this application, and those skilled in the art can obtain other drawings based on these without requiring any creative effort. Here, [Figure 1] This is a schematic diagram of the structure of one embodiment relating to the fluorescent ceramics of the present invention. [Figure 2] This is a flowchart of one embodiment of the method for manufacturing fluorescent ceramics according to the present invention. [Figure 3] This is a microstructural image of the fluorescent ceramics produced in Example 2. [Modes for carrying out the invention]
[0012] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings of the embodiments of the present application. Clearly, the embodiments described are only a subset of the embodiments of the present application, not all of them. Any other embodiments that a person skilled in the art could conceive of based on the embodiments of the present application without requiring creative effort are all included within the scope of the present application.
[0013] Referring to Figure 1, Figure 1 is a schematic diagram of the configuration of one embodiment relating to the fluorescent ceramic of the present application, which includes at least a matrix 101, an emission center 102, a first scattering unit 103, and a second scattering unit 104. The emission center 102, the first scattering unit 103, and the second scattering unit 104 are distributed within the matrix 101.
[0014] Here, the matrix 101 may be manufactured from a ceramic raw material, which may include one of aluminum oxide, aluminum nitride, silicon carbide, silicon nitride, or zirconium oxide. These materials are characterized by a low refractive index, high thermal conductivity, high light transmittance, and resistance to the temperature during subsequent sintering. In other embodiments, the matrix 101 may be a cubic transparent ceramic with a garnet structure, and the luminescence center 102 may be a fluorescent powder with a garnet structure. When both the luminescence center 102 and the matrix 101 have a garnet structure, the luminescence performance and mechanical performance of the fluorescent ceramic can be optimized.
[0015] Preferably, the matrix 101 is an aluminum oxide matrix, and the luminescence center 102 is a fluorescent powder. Here, aluminum oxide belongs to the trigonal crystal system and birefringence occurs, so grain boundary birefringence occurs in the aluminum oxide matrix, and the incident laser light is scattered by grain boundary birefringence in the fluorescent ceramics. The scattered incident laser light can excite more luminescence centers in its vicinity, further improving the luminescence efficiency.
[0016] Furthermore, during a long period of research and development, the inventors of this application discovered that the refractive index of the aluminum oxide matrix and the refractive index of the fluorescent powder are both 1.7 to 1.8, which are very close. As a result, the refraction or scattering effect of the incident laser light and fluorescence within the fluorescent ceramic is weak, and the light is easily conducted laterally to the surroundings. Consequently, the fluorescence spot of the fluorescent ceramic becomes large, and when the diffusion of the light spot is large, the collection efficiency of the collecting lens is low, affecting the optical efficiency utilization rate of the light source system.
[0017] Considering that particle scattering ability depends on the particle dimensions and relative refractive index, the inventors of the present invention provide a two-phase fluorescent ceramic based on aluminum oxide-fluorescent powder, in which at least first and second scattering units are distributed in the matrix, the refractive index of the first scattering unit being greater than that of the luminescence center, and the refractive index of the second scattering unit being smaller than that of the luminescence center. Due to the large difference in refractive index between the first scattering unit, the luminescence center, and the second scattering unit within the fluorescent ceramic (as can be understood, the refractive index of the matrix is close to that of the luminescence center, and the difference in refractive index between the first and second scattering units and the matrix is also large), the scattering generated at the interface of each phase of the incident laser light is enhanced. By enhancing the refraction and scattering effects of the fluorescent ceramics with respect to the incident laser light and fluorescence within them, the optical path length of the excitation light in the ceramics is increased, and the lateral conduction of fluorescence within the fluorescent ceramics is weakened. As a result, the fluorescence is ultimately scattered from a small area near the incident laser light, i.e., the generated fluorescence spot is smaller, further improving the scattering performance of the fluorescent ceramics for fluorescence and increasing the optical efficiency utilization rate in the light source system.
[0018] Furthermore, when selecting the materials of the different light-emitting centers 102, the first scattering unit 103, and the second scattering unit 104, the refractive index differences between the first scattering unit 103 and the light-emitting center 102 and between the second scattering unit 104 and the light-emitting center 102 are different and are not specifically limited. Here, the refractive index difference between the first scattering unit 103 and the light-emitting center 102 may be 0.01 to 2.0, for example, 0.01, 0.4, 0.6, 0.8, or 2.0. The refractive index difference between the second scattering unit 104 and the light-emitting center 102 may be 0.01 to 2.0, for example, 0.01, 0.4, 0.6, 0.8, or 2.0.
[0019] Different from the prior art, in the present application, the light-emitting center, the first scattering unit, and the second scattering unit having different refractive indices are uniformly distributed in the matrix of the fluorescent ceramics, and the refractive index of the first scattering unit is greater than the refractive index of the light-emitting center, and the refractive index of the second scattering unit is smaller than the refractive index of the light-emitting center. Since the particle scattering ability depends on the dimension and relative refractive index of the particles, and the incident laser light is scattered at the interface of each phase, the refraction and scattering effects on the incident laser light and fluorescence inside the fluorescent ceramics can be enhanced, the optical path length of the excitation light in the ceramics can be lengthened, and further the lateral conduction of the fluorescence inside the fluorescent ceramics can be weakened, so that the fluorescence is finally scattered from a small range of regions near the incident laser light, that is, the generated fluorescence spot is small, and further the scattering performance of the fluorescence of the fluorescent ceramics is improved, and the light efficiency utilization rate in the light source system is improved.
[0020] In one embodiment, the first scattering unit 103 is at least one of pores or first scattering particles.
[0021] Here, the refractive index of the above pores is 1, and when the particle size of the pores is 0.2 to 2 μm, the scattering effect on the excitation light source is high. The particle size of the pores may be 0.2 μm, 0.8 μm, 1.0 μm, or 2.0 μm.
[0022] Note that the pore size in this embodiment refers to the diameter of the pore when the pore is spherical, and when the pore is non-spherical, the pore size is the diameter of the minimum circumscribed sphere of the pore.
[0023] In order to avoid the light transmittance of the fluorescent ceramics being affected by too many or too few pores, in this embodiment, the volume fraction of pores in the fluorescent ceramics is 0.01% to 10%, for example, it is 0.01%, 0.1%, 1%, 5% or 10%.
[0024] In one embodiment, the refractive index of the first scattering particles is 1.2 to 3.5, for example, it is 1.2, 1.7, 2.1, 2.5 or 3.5. The first scattering particles account for 0.1% to 1% of the total mass of the fluorescent ceramics, for example, they account for 0.1%, 0.5%, 0.8% or 1%.
[0025] Here, the first scattering particles may be at least one of titanium dioxide, zirconium oxide, yttrium oxide, calcium fluoride or magnesium fluoride .
[0026] Furthermore, the second scattering unit 104 may be at least one of pores or second scattering particles.
[0027] Here, the refractive index of the pores is 1, and when the pore size is 0.2 to 2 μm, the scattering effect on the excitation light source is high. The pore size may be <0000
[0028] 108>0.2 μm, 0.8 μm, 1.0 μm or
[0029] 2.0 μm .
[0028] Note that the pore size in this embodiment refers to the diameter of the pore when the pore is spherical, and when the pore is non-spherical, the pore size is the diameter of the minimum circumscribed sphere of the pore.
[0029] In order to avoid the light transmittance of the fluorescent ceramics being affected by too many or too few pores, in this embodiment, the volume fraction of pores in the fluorescent ceramics is 0.01% to 10%, for example, it is 0.01%, 0.1%, 1%, 5% or 10%.
[0030] In one embodiment, the refractive index of the second scattering particle is 1.2 to 2.5, for example, 1.2, 1.4, 1.6, 1.8, or 2.5. The second scattering particle accounts for 0.1% to 1% of the total mass of the fluorescent ceramic, for example, 0.1%, 0.5%, 0.8%, or 1%.
[0031] Here, the second scattering particle is at least one of calcium fluoride, magnesium fluoride, yttrium oxide, or zirconium oxide.
[0032] In one embodiment, in order to further improve the scattering effect of the fluorescent ceramics, the fluorescent ceramics further include a third scattering unit (not shown) distributed within the matrix 101. Here, the refractive index of the third scattering unit is between the refractive index of the first scattering unit 103 and the refractive index of the second scattering unit 104.
[0033] Furthermore, when selecting different materials for the light emission center 102, the first scattering unit 103, the second scattering unit 104, and the third scattering unit, the refractive index difference between the first scattering unit 103 and the third scattering unit, the refractive index difference between the second scattering unit 104 and the third scattering unit, and the refractive index difference between the light emission center and the third scattering unit are different and not specifically limited. Here, the absolute difference between the refractive index of the third scattering unit and the refractive index of the first scattering unit 103 is 0.6 to 1.5, for example, 0.6, 0.8, 1.0, or 1.5. The absolute difference between the refractive index of the third scattering unit and the refractive index of the second scattering unit 104 is 0.6 to 1.5, for example, 0.6, 0.8, 1.0, or 1.5.
[0034] Specifically, the third scattering unit is at least one of pores or third scattering particles. The refractive index of the third scattering particles is 1.2 to 2.5, for example, 1.2, 1.4, 1.6, 1.8, or 2.5. The third scattering particles account for 0.1% to 1% of the total mass of the fluorescent ceramics, for example, 0.1%, 0.5%, 0.8%, or 1%.
[0035] In one embodiment, the luminescence center 102 is a lanthanide element-doped YAG phosphor particle with a particle size of 5 μm to 30 μm, for example, 5 μm, 10 μm, 20 μm, or 30 μm. The doping amount is 1% to 5%, for example, 1%, 2%, 3%, or 5%. The lanthanide element-doped YAG phosphor particles account for 40% to 50% of the total mass of the fluorescent ceramic, for example, 40%, 42%, 45%, or 50%.
[0036] Specifically, to make it easier to understand, if there is not a sufficient amount of fluorescent powder as the luminescence center 102, the luminescence intensity of the fluorescent ceramic cannot be guaranteed. When lanthanide element-doped YAG phosphor particles account for 40% to 50% of the total mass of the fluorescent ceramic, they have luminescence centers 102 with a large crystal grain size, improving luminescence efficiency, and are free of impurity phases, have pure grain boundaries, and have high optical uniformity, meeting the demands of use with high-power light sources such as incident laser light. Furthermore, because scattering particles are added, when the incident laser light is irradiated with the scattering particles, the excitation light source is scattered, and after the excitation light source is scattered, the optical path length of the excitation light in the ceramic becomes longer, thereby improving the optical conversion efficiency.
[0037] The material of matrix 101 is aluminum oxide with a particle size of 0.05 μm to 1 μm, for example, 0.05 μm, 0.1 μm, 0.5 μm, or 1.0 μm. The aluminum oxide accounts for 40% to 60% of the total mass of the fluorescent ceramics, for example, 40%, 50%, 55%, or 60%.
[0038] In one embodiment, the lanthanide element-doped YAG phosphor particles are YAG phosphor particles doped with Ce or Lu.
[0039] Specifically, the manufacturing formulation employed in this embodiment involves doping the YAG matrix 101 with 1% to 5% Ce, although in other embodiments, Lu may be used instead. This allows the YAG matrix 101 to emit light, supplementing the emission of the fluorescent ceramics. In this embodiment, the YAG matrix 101 is used as an adhesive medium to bond large-grained YAG phosphor particles. By further adjusting the doping content of Ce or Lu in the adhesive medium, it is possible to adjust the color coordinates of the fluorescent ceramics within a certain range. The doping content in the YAG matrix 101 and the large-grained YAG phosphor particles differs, resulting in different fluorescence spectral ranges. These two complement each other, improving the color development by incident laser light. Furthermore, high refractive index scattering particles are uniformly distributed in the fluorescent ceramics. When incident laser light is irradiated onto the scattering particles, the excitation light source is scattered. After the excitation light source is scattered, the optical path length of the excitation light in the ceramics increases, improving the light conversion efficiency.
[0040] Figure 2 is a flowchart of one embodiment of the method for manufacturing fluorescent ceramics according to the present invention. The present invention further provides a method for manufacturing fluorescent ceramics, the manufacturing method comprising the following steps. In S10, the matrix material, scattering material, and phosphor particles of the fluorescent ceramics are prepared in predetermined ratios.
[0041] Specifically, the matrix material can be aluminum oxide with a purity of 99.0% and a particle size of 0.05 μm to 1 μm. The phosphor particles can be lanthanide element-doped YAG phosphor particles with a purity of 99.0% and a particle size of 5 μm to 30 μm.
[0042] Here, the scattering material includes at least a pore-forming agent and first scattering particles and second scattering particles.
[0043] The pore-forming agent is starch (particle size 0.1 μm to 10 μm, e.g., 0.1 μm, 1 μm, 10 μm) or PMMA microspheres (particle size 0.1 μm to 10 μm, e.g., 0.1 μm, 1 μm, 10 μm). The first scattering particle can be selected from at least one of titanium dioxide, zirconium oxide, yttrium oxide, calcium fluoride, or magnesium fluoride with a purity of 99.0%. The second scattering particle can be selected from at least one of calcium fluoride, magnesium fluoride, yttrium oxide, or zirconium oxide with a purity of 99.0%.
[0044] In step S20, the matrix material and the scattering material are mixed in the first solvent and ball-milled to obtain the first ball mill slurry.
[0045] Specifically, the matrix material and the scattering material are mixed in predetermined ratios, and the mixture is placed in a ball milling tank with the first solvent as the liquid phase medium. Ball milling is performed, the rotation speed of the ball milling is set to 120 r / min to 300 r / min, and ball milling is carried out for 1 to 4 hours to obtain the first ball mill slurry. The first solvent may be a mixture containing one or more of the following: silicone oils of various systems such as phenyl groups and methyl groups, ethanol, ethylene glycol, xylene, ethylcellulose, terpineol, butyl carbitol, PVA, PVB, PAA, and PEG.
[0046] In S30, the phosphor particles are mixed with the second solvent and ball milled to obtain a second ball mill slurry.
[0047] Specifically, using the first solvent as a liquid-phase medium, phosphor particles are placed in a ball milling tank, ball milling is performed, the ball milling rotation speed is set to 120 r / min to 300 r / min, and ball milling is carried out for 0.5 h to 4 h to obtain a second ball mill slurry. The second solvent may be a mixture containing one or more of the following: silicone oils of various systems such as phenyl groups and methyl groups, ethanol, ethylene glycol, xylene, ethylcellulose, terpineol, butyl carbitol, PVA, PVB, PAA, and PEG.
[0048] In step S40, the first ball mill slurry and the second ball mill slurry are dried separately, and after drying, they are polished and sieved to obtain the first powder and the second powder.
[0049] Specifically, before drying, the first ball mill slurry and the second ball mill slurry are vacuum degassed to obtain low-bubble, and ultimately bubble-free, first and second ball mill slurries suitable for casting. The first and second ball mill slurries are dried at a constant vacuum temperature to obtain dried powder, the dried powder is calcined in a muffle furnace to remove organic components from the dried powder, and then the powder is sieved and granulated to obtain the first powder and the second powder.
[0050] In step S50, the first powder and the second powder are mixed, and the mixed powder is pressed to obtain a pre-molded product.
[0051] Specifically, appropriate amounts of the first and second powders are weighed and placed in a graphite mold, and the mixed powder is pressed. The pressing method is not particularly limited and can be carried out using a normal pressing method, such as cold isostatic pressing. The pressing pressure is usually 5 MPa to 200 MPa, preferably 15 MPa to 100 MPa. If the pressure is too low, the pores will be numerous and large, affecting the density of the final sintered product.
[0052] In S60, the base material is obtained by performing a high-temperature adhesive discharge treatment on the pre-molded product. Specifically, the crucible containing the pre-molded product is placed in a position close to the thermocouple in the muffle furnace to initiate the adhesive removal process. The adhesive removal process is as follows: The temperature is raised to 200°C at a heating rate of 0.3°C / min to 0.6°C / min and held for 0 to 2 hours to remove moisture such as free water and crystal water from the material. The temperature is then raised to 500°C at a heating rate of 0.4°C / min to 0.7°C / min and held for 0 to 3 hours to decompose and volatilize organic matter in the material. The temperature is then raised to the densification temperature at a heating rate of 0.4°C / min to 0.7°C / min and held for 2 to 6 hours. Through this process, the ceramic material can develop a certain strength and will not collapse. The densification temperature is generally set to a temperature 300°C to 1000°C lower than the sintering temperature of the ceramic, avoiding the sintering process between the raw material powder and the ceramic material, and contributing to the removal of raw material powder. The cooling method is furnace cooling, and the atmosphere is atmospheric air. The adhesive removal process not only removes moisture and organic matter from the substrate, but also causes uniform shrinkage of the substrate, achieving a certain level of densification. The volume shrinkage is 4% to 30%, and the weight reduction is 20% to 50%.
[0053] In S70, the substrate is subjected to cold isostatic pressure treatment. Specifically, after the adhesive has been removed, the fluorescent ceramic substrate is subjected to cold isostatic pressure treatment at a pressure of 150 MPa to 200 MPa to improve the density of the ceramic substrate.
[0054] In S80, a substrate that has undergone cold isostatic pressure treatment is subjected to high-temperature sintering, and after polishing, fluorescent ceramics are obtained.
[0055] The ceramic body, with the adhesive cleanly removed, is placed back into the muffle furnace and heated to the sintering temperature at a heating rate of 1°C / min to 3°C / min. After being kept warm for 1 to 12 hours, the atmosphere is changed to air, and the furnace is cooled to room temperature. After polishing, fluorescent ceramics are obtained.
[0056] Fluorescent ceramics are obtained after heat treatment, and the manufacturing method further includes a reduction treatment step for the fluorescent ceramics, which is carried out in a reducing atmosphere (e.g., a nitrogen gas / hydrogen gas mixture), at a temperature slightly lower than the heat treatment sintering temperature, with the reduction temperature being 1200°C to 1650°C. This reduction treatment process can remove impurities attached to the fluorescent ceramics in the heat treatment step, preventing the impurities from becoming heat sources in the operating environment of the fluorescent ceramics and affecting their use.
[0057] Preferably, the matrix of the fluorescent ceramic may be an aluminum oxide matrix, and the luminescence centers are fluorescent powders. Since aluminum oxide belongs to the trigonal crystal system and exhibits birefringence, grain boundary birefringence exists in the aluminum oxide matrix fluorescent ceramic. The incident laser light is scattered by grain boundary birefringence in the fluorescent ceramic, and the scattered incident laser light can excite more luminescence centers in its vicinity, further improving the luminescence efficiency.
[0058] Furthermore, during a long period of research and development, the inventors of this application discovered that the refractive index of the aluminum oxide matrix and the refractive index of the fluorescent powder are both 1.7 to 1.8, which are very close. As a result, the refraction or scattering effect of the incident laser light and fluorescence within the fluorescent ceramic is weak, and the light is easily conducted laterally to the surroundings. Consequently, the fluorescence spot of the fluorescent ceramic becomes large, and when the diffusion of the light spot is large, the collection efficiency of the collecting lens is low, affecting the optical efficiency utilization rate of the light source system.
[0059] Considering that particle scattering ability depends on the particle dimensions and relative refractive index, the inventors of the present invention provide a two-phase fluorescent ceramic based on aluminum oxide-fluorescent powder, in which at least first and second scattering units are distributed in the matrix, the refractive index of the first scattering unit being greater than that of the luminescence center, and the refractive index of the second scattering unit being smaller than that of the luminescence center. Due to the large difference in refractive index between the first scattering unit, the luminescence center, and the second scattering unit within the fluorescent ceramic (as can be understood, the refractive index of the matrix and the luminescence center are close, and the difference in refractive index between the first and second scattering units and the matrix is also large), the scattering generated at the interface of each phase of the incident laser light is enhanced. By enhancing the refraction and scattering effects of the fluorescent ceramics with respect to the incident laser light and fluorescence within them, the optical path length of the excitation light in the ceramics is increased, and the lateral conduction of fluorescence within the fluorescent ceramics is weakened. As a result, the fluorescence is ultimately scattered from a small area near the incident laser light, i.e., the generated fluorescence spot is smaller, further improving the scattering performance of the fluorescent ceramics for fluorescence and increasing the optical efficiency utilization rate in the light source system.
[0060] Unlike the conventional technology, in this invention, the luminescence center, first scattering unit, and second scattering unit, each having a different refractive index, are uniformly distributed in the matrix of the fluorescent ceramics, with the refractive index of the first scattering unit being greater than that of the luminescence center and the refractive index of the second scattering unit being smaller than that of the luminescence center. Since the particle scattering ability depends on the particle dimensions and relative refractive index, and the incident laser light is scattered at the interface of each phase, the refraction and scattering effects of the fluorescent ceramics with respect to the incident laser light and fluorescence within them can be enhanced, increasing the optical path length of the excitation light in the ceramics, further weakening the lateral conduction of fluorescence within the fluorescent ceramics, and ultimately scattering the fluorescence from a small area near the incident laser light, i.e., the generated fluorescence spot is small, further improving the scattering performance of the fluorescent ceramics with respect to fluorescence and improving the optical efficiency utilization rate in the light source system.
[0061] The present application will be described in detail below with further examples. Similarly, the following examples are merely illustrative and should not be understood as limiting the scope of protection of the present application. Any non-essential improvements and adjustments made by those skilled in the art based on the above-mentioned content of the present application are all included within the scope of protection. The specific process parameters, etc., in the following examples are merely examples of an appropriate range; that is, those skilled in the art can select within an appropriate range as described herein and are not limited to the specific numerical values in the following examples.
[0062] Example 1 Aluminum oxide powder, zirconium oxide powder, and magnesium fluoride powder with a purity of 99.0% or higher are selected. 99.0% aluminum oxide powder, 0.5% zirconium oxide powder, and 0.5% magnesium fluoride powder are weighed according to their mass percentages. The mixed powder raw materials are then polished using a wet ball milling method with anhydrous ethanol as the medium, and the ball milling time is set to 24 hours to obtain the first ball mill slurry.
[0063] YAG:Ce fluorescent powder is weighed, where YAG:Ce fluorescent powder accounts for 50% of the total mass of the fluorescent ceramic powder. The mixed powder raw material is then polished using a wet ball mill method with a PVB ethanol solution as the medium, and the ball milling time is set to 1 hour to obtain a second ball mill slurry. Here, the mass percentage of PVB in the PVB ethanol solution is 0.5% to 2%. Mass percentage refers to the percentage of the mass of a substance relative to the total mass, and here it refers to the percentage of the mass of PVB relative to the total mass of the solution consisting of PVB and ethanol.
[0064] The powder is vacuum-dried at 70°C, immediately polished, sieved, and then packaged for use.
[0065] A block is manufactured by pressing a mixed fluorescent ceramic powder at a pressure of 80 MPa. The molded ceramic substrate is then subjected to adhesive removal treatment in a muffle furnace, which involves heating at 500°C for 2 hours and then at 900°C for 4 hours. After adhesive removal, the fluorescent ceramic substrate is subjected to cold isostatic pressure treatment at a pressure of 200 MPa to improve the density of the ceramic substrate.
[0066] The ceramic substrate is placed in a vacuum furnace, and the vacuum level is set to 10 -3 The material is set to Pa and sintered at 1650°C for 4 hours. After vacuum sintering, the fluorescent ceramics are annealed in an air atmosphere at 1300°C for 10 hours, and then thinned and polished to obtain usable fluorescent ceramics.
[0067] Example 2 Aluminum oxide powder with a purity of 99.9% or higher, titanium oxide with a purity of 99%, and a pore-forming agent are selected. According to the mass percentage, 98.0% aluminum oxide powder, 1.0% titanium oxide powder, and 1.0% pore-forming agent are weighed out, and the mixed powder raw materials are polished using anhydrous ethanol as a medium. The ball milling time is set to 24 hours to obtain the first ball mill slurry.
[0068] YAG:Ce fluorescent powder is weighed, where YAG:Ce fluorescent powder accounts for 40% of the total mass of the fluorescent ceramic powder. The mixed powder raw material is then polished using a wet ball mill method with a PVB ethanol solution as the medium, and the ball milling time is set to 0.5 hours to obtain a second ball mill slurry. Here, the mass percentage of PVB in the PVB ethanol solution is 0.5% to 2%. Mass percentage refers to the percentage of the mass of a substance relative to the total mass, and here it refers to the percentage of the mass of PVB relative to the total mass of the solution consisting of PVB and ethanol.
[0069] The powder is vacuum-dried at 60°C, immediately polished, sieved, and then packaged for use.
[0070] A block is manufactured by pressing a mixed fluorescent ceramic powder at a pressure of 50 MPa. The molded ceramic substrate is then subjected to adhesive removal treatment in a muffle furnace, which involves heating at 600°C for 2 hours and then at 1000°C for 6 hours. After adhesive removal, the fluorescent ceramic substrate is subjected to cold isostatic pressure treatment at a pressure of 180 MPa to improve the density of the ceramic substrate.
[0071] The ceramic substrate is placed in a vacuum furnace, and the vacuum level is set to 10 -3 The material is set to Pa and sintered at 1600°C for 4 hours. After vacuum sintering, the fluorescent ceramics are annealed in an air atmosphere at 1350°C for 10 hours, and then thinned and polished to obtain usable fluorescent ceramics.
[0072] Referring to Figure 3, Figure 3 is a microstructural photograph of the fluorescent ceramics produced in Example 2. As can be seen from the figure, the uniformly dispersed phosphor particles in the aluminum oxide ceramic matrix have been removed, and a small amount of low refractive index phase (porosity) and high refractive index phase (titanium oxide) remain.
[0073] Example 3 Aluminum oxide powder with a purity of 99.9% or higher, magnesium fluoride, titanium oxide, and zirconium oxide are selected. Based on their mass percentages, 99.0% aluminum oxide powder, 0.30% magnesium fluoride, 0.30% titanium oxide, and 0.40% zirconium oxide are weighed out. The mixed powder raw materials are then polished using a wet ball milling method with anhydrous ethanol as the medium, and the ball milling time is set to 36 hours to obtain the first ball mill slurry.
[0074] YAG:Ce fluorescent powder is weighed, where YAG:Ce fluorescent powder accounts for 60% of the total mass of the fluorescent ceramic powder. The mixed powder raw material is then polished using a wet ball mill method with a PVB ethanol solution as the medium, and the ball milling time is set to 0.5 hours to obtain a second ball mill slurry. Here, the mass percentage of PVB in the PVB ethanol solution is 0.5% to 2%. Mass percentage refers to the percentage of the mass of a substance relative to the total mass, and here it refers to the percentage of the mass of PVB relative to the total mass of the solution consisting of PVB and ethanol.
[0075] The powder is vacuum-dried at 70°C, immediately polished, sieved, and then packaged for use.
[0076] Ceramic powder is filled into a graphite mold and pre-pressed at a pressure of 5-20 MPa. The graphite mold is then placed in an SPS hot press furnace and sintered in a vacuum / argon atmosphere at 1200°C-1600°C for 0.5-4 hours, with a sintering pressure of 20-150 MPa. After hot press sintering, the fluorescent ceramics are annealed in an air atmosphere at 1300°C for 10 hours. Further thinning and polishing treatments are then performed on the fluorescent ceramics to obtain usable fluorescent ceramics.
[0077] Comparative Example Aluminum oxide powder and YAG:Ce fluorescent powder with a purity of 99.9% or higher are selected. 50.0% aluminum oxide powder and 50.0% YAG:Ce fluorescent powder are weighed according to their mass percentages. The mixed powder raw materials are then polished using a wet ball milling method with anhydrous ethanol as the medium, and the ball milling time is set to 36 hours to obtain a slurry.
[0078] The powder is vacuum-dried at 70°C, immediately polished, sieved, and then packaged for use.
[0079] Ceramic powder is filled into a graphite mold and pre-pressed at a pressure of 50 MPa to 20 MPa. Then the graphite mold is placed in an SPS hot press furnace and sintered in a vacuum / argon atmosphere at 1200°C to 1600°C for 0.5 to 4 hours, with a sintering pressure of 200 MPa to 150 MPa. After hot press sintering, the fluorescent ceramics are annealed in an air atmosphere at 1300°C for 10 hours, and then thinned and polished to obtain usable fluorescent ceramics.
[0080] Example 4 Fluorescent ceramics manufactured in Examples 1, 2, and 3, as well as unoptimized fluorescent ceramics (i.e., comparative examples), were processed into test samples, placed on a test platform, and compared. The test results are shown in the table below. In the table, luminous efficiency refers specifically to the conversion efficiency of the optical power of the blue incident laser light.
[0081] [Table 1]
[0082] As can be seen from the table above, in Examples 1 to 3, the luminescence center, first scattering unit, and second scattering unit, each having a different refractive index, are uniformly distributed in the matrix of the fluorescent ceramics. Furthermore, the difference in refractive index between the first scattering unit, the luminescence center, and the first scattering unit within the matrix is large (as can be understood, since the refractive index of the matrix is close to that of the luminescence center, the difference in refractive index between the first and second scattering units and the matrix is also large). As a result, the particle scattering ability depends on the particle dimensions and relative refractive index, and the incident laser light is scattered at the interface of each phase. This enhances the refraction and scattering effect of the fluorescent ceramics on the incident laser light and fluorescence within them, thereby increasing the optical path length of the excitation light in the ceramics, further weakening the lateral conduction of fluorescence within the fluorescent ceramics, and ultimately scattering the fluorescence from a small area near the incident laser light. That is, the generated fluorescence spot is small, further improving the scattering performance of the fluorescent ceramics on fluorescence and improving the optical efficiency utilization rate in the light source system.
[0083] The present invention further provides a light-emitting device comprising an excitation light source and the fluorescent ceramics, wherein the excitation light source is an incident laser light source, and the excitation light source irradiates the fluorescent ceramics to generate high-brightness light. The light-emitting device may be applied to projection and display systems, such as liquid crystal displays (LCDs) or digital light processors (DLPs), to lighting systems, such as automotive lighting, or to the field of 3D display technology. In the light-emitting device, the fluorescent ceramics can be manufactured as a movable device, such as a color wheel, and incident laser light is generated by irradiating the rotating color wheel with the excitation light source emitted by the excitation light source.
[0084] The present invention further provides a projection device, which may be an educational projector, an incident laser television, a microprojector, or a broadcasting machine, and which includes the light-emitting device of the above embodiment, the specific configuration of the light-emitting device shall refer to the above embodiment.
[0085] The foregoing are merely embodiments of the present application and do not limit the scope of the claims of the present application. Equivalent configurations or equivalent flow transformations performed using the contents of the specification and drawings of the present application, or their direct or indirect application to other related technical fields, are all similarly included within the scope of the claims of the present application.
Claims
1. A fluorescent ceramic, The fluorescent ceramic includes at least a matrix, a luminescent center, a first scattering unit, and a second scattering unit distributed in the matrix, The refractive index of the first scattering unit is greater than the refractive index of the luminescent center; The refractive index of the second scattering unit is smaller than the refractive index of the luminescent center; the matrix is an aluminum oxide matrix, the luminescent center is a YAG phosphor particle doped with a lanthanide element, The first scattering unit is a first scattering particle, and the refractive index of the first scattering particle is 2.1 to 3.5; The fluorescent ceramics, characterized in that the second scattering units are second scattering particles or pores, the refractive index of the second scattering particles is 1.2 to 1.6, and the refractive index of the pores is 1.
2. A fluorescent ceramic as described in claim 1, characterized in that the particle size of the pores is 0.2 μm to 2 μm, and the volume fraction of the pores in the fluorescent ceramic is 0.01% to 10%.
3. The fluorescent ceramic described in claim 1, characterized in that the mass of the first scattering particles accounts for 0.1% to 1% of the total mass of the fluorescent ceramic.
4. 2. The fluorescent ceramic of claim 1, wherein the first scattering particles are titanium dioxide, zirconium oxide, or a combination of titanium dioxide and zirconium oxide.
5. The fluorescent ceramic described in claim 1, characterized in that the mass of the second scattering particles accounts for 0.1% to 1% of the total mass of the fluorescent ceramic.
6. 2. The fluorescent ceramic of claim 1, wherein the second scattering particles are calcium fluoride, magnesium fluoride, or a combination of calcium fluoride and magnesium fluoride.
7. 2. The fluorescent ceramic of claim 1, further comprising a third refractive index unit, the third refractive index unit being distributed within the matrix and having a refractive index between the refractive index of the first scattering unit and the refractive index of the second scattering unit.
8. the luminescence center is a lanthanide-doped YAG phosphor particle having a particle size of 5 μm to 30 μm, the doping amount is 1% to 5%, and the mass of the lanthanide-doped YAG phosphor particle accounts for 40% to 50% of the total mass of the fluorescent ceramic; 2. The fluorescent ceramic according to claim 1, wherein the matrix material is aluminum oxide having a grain size of 0.05 μm to 1 μm, and the mass of the aluminum oxide accounts for 40% to 60% of the total mass of the fluorescent ceramic.
9. 9. The fluorescent ceramic according to claim 8, wherein the lanthanoid-doped YAG phosphor particles are YAG phosphor particles doped with Ce or Lu.
10. A method for producing a fluorescent ceramic, the fluorescent ceramic being the fluorescent ceramic according to any one of claims 1 to 9, The manufacturing method includes: A matrix material of a fluorescent ceramic, a scattering material and phosphor particles are prepared in a predetermined ratio, where the scattering material includes at least a pore former and a first scattering particle, a second scattering particle, and a second scattering particle. and mixing the matrix material and the scattering material in a first solvent and ball milling the mixture to obtain a first ball milled slurry; mixing the phosphor particles in a second solvent and ball milling the mixture to obtain a second ball mill slurry; drying the first ball mill slurry and the second ball mill slurry, respectively, and then pulverizing and sieving the first and second powders; mixing the first powder and the second powder and pressing the mixed powder to obtain a preform; subjecting the preform to a high-temperature degreasing treatment to obtain a green body; subjecting the base material to cold isostatic pressing; and subjecting the cold isostatically pressed base material to a high-temperature sintering treatment and polishing, and then obtaining the fluorescent ceramics.
11. 1. A light emitting device, comprising: A light emitting device comprising an excitation light source and the fluorescent ceramic according to any one of claims 1 to 9, wherein the excitation light source is an incident laser light source.
12. 1. A projection device, comprising: A projection device comprising the light emitting device according to claim 11.